Analysis of the Effectiveness of Credit Granting Procedures in the Homestay Business Sector Fostered by KSP Kopdit Obor Mas - Karolina Aprila Dua Meak; Henrikus Herdi; Siktania Maria Diliana; Yuliana Anggreani Dua Delang Kolit (International Publisher (YAPENBI), 2024)
This study aims to determine the effectiveness of credit granting procedures in the homestay business field assisted by KSP Kopdit Obor Mas. It uses a qualitative descriptive approach with case studies. The data in this study were obtained through primary data sources. The data collection methods are interviews and observations. The data needed in this study is the credit report of KSP Kopdit Obor Mas Ngada Main Branch. The results show that the 5 C Method implemented by KSP Kopdit Obor Mas effectively assesses the feasibility of providing credit to members, ensuring that loans are only given to members who meet the set criteria. Compliance with credit application procedures at KSP Kopdit Obor Mas Ngada Main Branch helps minimize the risk of non-performing loans and increases transparency in the credit granting process. The level of compliance of borrower members in credit repayment shows that the provision of credit to the Homestay Vernando business is effective, with stable returns and good business management.